A reinforced energy-absorbing structure formed by combining multiple aluminum foam-filled open-hole tubes. (15th June 2022) - Xie, Suchao; Zhang, Jing; Liu, Xiang; Zheng, Shiwei; Liu, Zinan
Highlights: Crashworthiness of aluminum foam-filled open-hole tubes (AFOTs) was studied. A collaborative innovation combination mode based on AFOTs was proposed. Multi-tube combined structures reduce the fluctuation of peak and valley values. The MCF of the four-AFOT combined structure is increased by 28.11%. The ULC of the four-AFOT combined structure is reduced by 66.09%. Abstract: In order to improve the energy absorption (EA) performance of thin-walled structures and overcome defects of a large peak impact force and large load fluctuation of multi-tube combined structures, the crashworthiness of aluminum foam-filled open-hole tubes (AFOTs) and their combined energy-absorbing structure was studied. Their EA performance was evaluated and effects of open-hole parameters including size, number and spacing of holes on axial compression characteristics were investigated through experiments and finite element analysis. The results indicate that the initiator of square holes can effectively reduce the initial peak crushing force (IPCF), but the reduced IPCF does not decrease exponentially with the increase of the number of holes, and the number and spacing of holes affect phases of wave crests and troughs on force–displacement curves. When at unequal spacings, the deformation mode of AFOTs changes in a sequence of extensional, mixed, and symmetric deformations with the increase in the spacing of the first hole. In view of wave crests and troughs with significant phase differences on force–displacement curves, a collaborative innovation combination mode based on AFOTs with different numbers and spacings of holes was proposed. A new, steady energy-absorbing structure, namely a structure combining four AFOTs, was developed by the combination of different numbers of tubes. In comparison with similar combined structures, the mean crushing force (MCF) is increased by 28.11% and the fluctuation in undulation of load-carrying capacity (ULC) is reduced by 66.09%. Graphical abstract: Image, graphical abstract